Disease burden of biliary tract cancer in 204 countries and territories, 1990–2021: A comprehensive demographic analysis of the Global Burden of Disease Study 2021 - Xuheng Sun; Jiangmei Liu; Wei Zhang; Yijun Wang; Yan Jiang; Lijun Wang; Yixin Zou; Yuxuan Xiao; Yongbing Xiang; Maolan Li; Maigeng Zhou; Yingbin Liu; et al. (Chinese Medical Journal)
Abstract. Background:. Biliary tract carcinomas (BTCs) are relatively rare but lethal primary malignant tumors derived from the biliary tract system. The burden of BTCs varies according to sex, age, region, and country, but limited attention has been paid to the burden of BTCs. We sought to explore the up-to-date data from the Global Burden of Disease Study (GBD) and expand findings by accessing the demographic features of BTC disease burden. Methods:. Using the latest data from the GBD 2021, we evaluated and analyzed the distributions and patterns of BTC disease burden in various age groups, sexes, regions, and countries. Results:. The number of incident cases, deaths, and disability-adjusted life-years (DALYs) tended to increase and peaked at 216,770 (95% uncertainty interval [UI]: 181,890–245,240), 171,960 (95% UI: 142,350–194,240), and 3,732,100 (95% UI: 3,102,900–4,317,000) person-years, respectively, in 2021. However, the average global age-standardized rates (ASRs) of incident cases, deaths, and DALYs shrunk by −11.46% (95% UI: −21.91 to 3.35%), −24.09% (95% UI: −33.19 to 16.88%), and −26.25% (95% UI: −35.53 to 18.36%), respectively, from 1990 to 2021. Meanwhile, the male/female ratio (male per 100 female) of incidence, deaths, and DALYs changed from 76.40, 75.41, and 74.72 to 86.89, 79.11, and 82.29, respectively. In 2021, the highest number of incident cases, deaths, and DALYs occurred in East Asia. The top three highest incidences, deaths, and DALYs were observed in China, India, and Japan, and the highest ASRs were observed in Chile in 2021. Analysis of the Human Development Index along with disease burden estimates of BTCs also suggests that the burden of the disease is related to the level of comprehensive development of the society. Conclusion:. This study provided a comprehensive comparison of differences in the burden of disease across populations and over time, and further presented evidence concerning the formulation of prevention and control policies and etiologic studies for BTCs and proposed logical hypotheses to investigate.